Renal Metastasis of Osteosarcoma with IVC Thrombus. (22nd March 2021) - Sigdel, Prem Raj; Gnyawali, Diwas; Parajuli, Purushottam; Chudal, Sampanna; Pandit, Durga; Guragain, Bipin; Pradhan, Manish Man; Poudyal, Sujeet; Chapagain, Suman; Luitel, Bhoj Raj; Chalise, Pawan Raj; Sharma, Uttam Kumar
Abstract : Renal metastasis from osteosarcoma is a rare entity, and tumour thrombus is even rarer. To date, only 15 cases of osteosarcoma with tumour thrombus have been reported in the literature. We present a case of an 18-year-old female diagnosed as having right distal femur osteosarcoma, later presenting with renal osteosarcoma with IVC thrombus.